Encountering the Age of Civility: The Late Ottoman Etiquette Literature (1890-1918) - Yasar, Fatma Tunc (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
This article explores the rise of etiquette books in late Ottoman world as a genre and analyses the emergence of this literature in late nineteenth century as the response of Ottomans to the age of civility in etiquette and lifestyle. It discusses the attitudes and approaches of the Ottoman authors in composing etiquette book, creating content and defining the etiquette by addressing the particular conditions of the late Ottoman socio-cultural milieu. By studying etiquette books as a genre representing the realms of aspirations, ideals and visions, this article reveals insights into how Ottoman authors defined the Ottoman etiquette under the increasing impact of European lifestyle and how they confronted, negotiated and coped with the predicaments of alla franca.
Keywords: Area Studies